Avaliação do esquema corporal em crianças com cegueira congênita : um estudo exploratório - Oliveira, Patricia Santos de (2011)
Body scheme is very important in the human development once the body is the center of integration and relationship with the world. A blind child, when not properly stimulated, may show alterations related to the structuring of the body scheme. Therefore, an early evaluation diagnosing alterations related to the psychomotor development of the child is extremely important. Several instruments evaluate the body scheme. However, most of them use visual information, which is hardly understood by a blind child. Therefore, the objective of this study was to elaborate and validate an instrument of evaluation of Body Scheme which is adequate to blind children. As methodological procedures, 5 children aged between 6 and 9 years old with congenital blindness, but without any other associated symptoms, and regularly enrolled in a specialized institution for visually impaired children were selected. This study was developed in three steps. The first one corresponds to the phase of construction of the instrument; the second one concerns the process of validation of content where the instrument has gone through and analysis of a committee composed of seven judges; the third one corresponds to the application of the instrument. Therefore, a version of the instrument composed of 4 items was elaborated. This version was sent to the committee who analyzed each item based on clarity of language, theoretical pertinence, viability of application and adequacy of construction. Item 1 Exploring the body obtained 80% agreement; item 2 Playing getting dressed received 70% agreement; item 3 Imitating gestures 60% agreement; item 4 Puzzle 75% agreement. The criterion of permanence of an item was a minimum of 80% agreement among the judges and this way, only item 1 remained as it was in the first version; item 2 was excluded and items 3 and 4 were modified. Based on the suggestions of the judges and the rate of agreement, a second version of the instrument composed of three items was elaborated and was applied as a pilot to the aforementioned population. The percentage of right responses of the five children was of 82%, 74%, 90%, 53%, 93% respectively. Through the observations made, some modifications related to the methodologies of applications have been proposed. Therefore it is possible to consider that the initial objective of the study has been achieved, once it has been possible to elaborate the instrument and validate its content by verifying its adequacy to blind children.